Ностальгия в системе базовых оппозиций „добро” и „зло” в автодокументальных произведениях Людмилы Улицкой „Детство 45–53: а завтра будет счастье” и Светланы Алексиевич „Время секонд хэнд” - Szewczenko, Ludmiła (Studia Rossica Posnaniensia, 2019)
The vision of the world portrayed in L. Ulitskaya’s and S. Alexievich’s books is built upon the basic opposition of good and evil. The category of prosthetic memory is juxtaposed with the personal experience of participants and witnesses of the past epoch who tell us about the past. The memories of the lost paradise of the serene years bring about narrators’ and responders’ nostalgia.